Areview of Dupuytren's Contracture in 43 Hands: Assessment of The Nature and Result After Fasciectomy - Dawood Jafari; Pouya Nozarnejad (Medical Journal of The Islamic Republic of Iran, 2010)
Background:Dupuytren's disease is a fibroproliferative disorder of the palmar fascia   that can result in disabling contractures of the digits. When function is impeded or deformity is disabling, surgical intervention can be considered, wherein a major problem is recurrence ( reported up to 74%). Although, the disease occurs predominantly in men of northern European, there are very few reports from African and Asian populations, especially from our country which may follow from the low prevalence in these areas. The purpose of this study was to examine the nature of the Dupuytren's disease and the recurrence rate after fasciectomy .   Methods: A hospital-based and cohort study design was used to recruit patients. Data   were gathered from the medical records and follow-up interviews with average 3 years ( ranges from 1 to 8 years), from all patients who underwent fasciectomy in our hospital from 1370 to 1388 .   Results: 29 patients (with 43 involved hands) have been admitted for surgical correction of Dupuytren's disease. Disease is more common (90% of cases) and appears significantly earlier in men. Right hand involves in 28% of the patients, left hand in 24% and both hands in 48%. The ring and the little fingers are involved most frequently. Association of Dupuytren's disease with the following factors was found: Manual labor in 68.97%, smoke in 31.03%, diabetes in 24.14%, alcohol in 17.24%, and epilepsy in 13.79%. The most common grade was found to be the grade II by using Tubiana's grade. Two patients with ectopic sites of the disease were found. The recurrence rate after fasciectomy in our patients is 9.38% (3 of 32 operated hands). From the recurrence risk factors, only bilateral disease involvement revealed to be significant in our patients .   Conclusion: Manifestations, pattern and severity of the disease were nearly comparable to those observed in the published studies, except for a lower prevalence rate and lower recurrence rate in our findings which are higher in the most studies. It seems that, the reason for this difference include genetics, pathogensis and other factors which may cause the disease and are still unclear .